PENERAPAN ALGORITMA DECISION TREE UNTUK PENENTUAN POLA PENERIMA BEASISWA KIP SISWA UPTD SMP NEGERI 4 SEKAMPUNG - Priyuli, Septika; Sugandi, Febri (Jurnal Mahasiswa Ilmu Komputer, 2024)
(1) School KIP is a program organized by the government with the aim of helping students pay for school and their lives. School KIP is distributed by the Ministry of Education, Culture, Research and Technology through schools in each region. Each school is given a different quota based on its level of development. The level of school development can be seen through each school's school program. The objectives of this research are: 1. Implement the Decision Tree algorithm to determine the pattern of KIP scholarship recipients for UPTD students at SMP Negeri 4 Sekampung. 2. Assist the UPTD of SMP Negeri 4 Sekampung to evaluate the KIP of students at their school. (2) The research method was carried out using KDD (Knowledge Discovery in Database). There are 5 steps in KDD, namely selection, pre-processing, transformation, data mining and evaluation (3) Data collection is carried out before carrying out the algorithm calculation process. The data used in this research came from participants receiving KIP UPTD Students at SMP Negeri 4 Sekampung for the 2023/2024 academic year. This study focused on a sample of 23 participants. The dataset consists of 23 data with 4 attributes and 1 target attribute. In the Raw data, the attributes used are Student Name, NIS, Class, Parents' Income, KIP Recipients, Poor Students & Orphaned Students. (4) The conclusion obtained from the research is that by carrying out the data mining process, data processing can be carried out again to obtain the information stored in the data. The results of the decision tree algorithm are in the form of decision trees and roles, the results obtained are in the form of rules that can be used in the decision making process.